PRODUCTION OF POLYCLONAL ANTIBODIES ANTI - IgM OF NILE TILAPIA, Oreochromis niloticus FOR STANDARDIZATION OF IMMUNOENZYMATIC ASSAY - CLISSA, P. B.; OREFICE, D. P.; COLOMBINI, M.; GUIMARÃES, M. C.; BACH, E. E.; DIAS, D. C.; TACHIBANA, L. (Ars Veterinaria, 2021)
In this letter, we describe the development of an immunodiagnostic assay capable of detecting specific IgM in the blood circulation of experimental Nile tilapia that received the vaccine against S. agalactiae.